Classroom Observations and the Power Relations between Academic Coordinators and Teachers in Feedback Sessions - Francisco Carlos Fogaça (The ESPecialist: Research in Language for Specific Purposes, 2011)
This article aims at discussing the power relations between academic coordinators of language schools and their teachers through the analysis of transcriptions of feedback sessions between coordinators and teachers after classroom observations, as part of a research project. Although power relations are often ignored by coordinators and school administrators, they may interfere with the professional development of language teachers. Instead of fostering reflection, feedback sessions may cause frustration and animosity if not properly conducted. This article will analyze how the understanding of power relations can help create better conditions for professional development.